2012
DOI: 10.1666/11014.1
|View full text |Cite
|
Sign up to set email alerts
|

Body size, longevity, and growth rate in Lake Pannon melanopsid gastropods and their predecessors

Abstract: We investigate potential microevolutionary mechanisms of phenotypic change in a lineage of brackish-water gastropods from Lake Pannon. The lineage exhibits a threefold increase in body size and a pronounced increase in shell shouldering over a roughly 2.5-Myr interval. We use the stable oxygen isotope profiles of 13 shells to address the question of whether large size is due to more rapid growth or to greater longevity.Results indicate that larger individuals have significantly greater longevity. Growth rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 109 publications
(115 reference statements)
0
13
0
1
Order By: Relevance
“…The only detailed study on size variation in a fossil brackish‐water gastropod lineage is provided by Geary et al . (). They demonstrated successive size increase in a melanopsid species lineage from Lake Pannon, interpreted as greater individual longevity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The only detailed study on size variation in a fossil brackish‐water gastropod lineage is provided by Geary et al . (). They demonstrated successive size increase in a melanopsid species lineage from Lake Pannon, interpreted as greater individual longevity.…”
Section: Discussionmentioning
confidence: 97%
“…Particularly among the families Lymnaeidae and Melanopsidae, several species lineages are famous for their outstandingly large shells (e.g. Moos, ; Geary et al ., ; Neubauer et al ., ). Members of the Valencienniinae, comprising large, low patelliform lymnaeids, attain maximum shell lengths of 125 mm (Moos, ).…”
Section: Introductionmentioning
confidence: 97%
“…The observed variability of the shell and the rich fossil record probably triggered interest in the group and resulted in quite a large number of studies being published since the beginning of the second half of the 20th Century. These studies focused largely on the underlying evolutionary processes that may have contributed to the observed morphological plasticity of the shell and also influenced the understanding of the paleobiogeography and historical biogeography of the family on different geographical scales (Papp, ; Geary, , ; Glaubrecht, , ; Heller et al., , ; Bandel, ; Heller and Sivan, , ,; Geary et al., , ; Elkarmi and Ismail, ; Bandel et al., ; Neubauer et al., , ,, ). It is therefore surprising that recent members of the group have received relatively little attention in morphology‐based or molecular phylogenetic studies until now, especially because the family, as currently understood, also exhibits an unparalleled Western Palearctic–Zealandian disjunct distribution pattern (see, e.g., Brot, ; Banarescu, ; Glaubrecht, , , ; Neiber and Glaubrecht, ).…”
Section: Introductionmentioning
confidence: 99%
“…L. soproniense, the largest specimen, appears to have the longest lifespan (at least 10 years). Geary et al (2012) observed that the Pannonian snail Melanopsis also seemed to achieve increased body size through increased longevity. They proposed that the reproductive advantage of larger body size coupled with an increase in resource availability and/or a decrease in predation drove this evolutionary trend in Melanopsis.…”
mentioning
confidence: 99%